McGraw-Hill encyclopedia of science and technology; Vol.20: Index (New York, 1997)
This book contains The Analytical Index, containing more than 170.000 entries; Topic Index, which lists all titles in a specific discipline; and Study Guides, outline the major fields of science and list corresponding articles of interest in the Encyclopedia
Keywords: science - encyclopedias,technology - encyclopedias